Heterogeneous drying of colloidal polymer films dependence on added salt - König, Alexander M (Langmuir : the ACS journal of surfaces and colloids, 2008)
Using magnetic resonance profiling coupled with dynamic light scattering, we have investigated the mechanisms leading to the formation of a partly coalesced surface layer, or "open skin", during film formation from waterborne polymer dispersions. We present the first use of the skewness of the distribution of free water as a model-free indicator of the spatial nonuniformity of drying. The skewness reaches a maximum at the same time at which a strong, static component, presumably originating from a skin at the film/air interface, appears in the light scattering data. Addition of salt to the dispersion increases both the skewness of the distribution of free water and the propensity for skin formation. Surprisingly, the drying is influenced not only by the concentration and valency of the ions in the salt but also by the particular ion. At intermediate particle densities, added salt strongly lowers the cooperative diffusion coefficient, Dcoop. When the particles reach close packing, Dcoop sharply increases. If the particles readily coalesce, the effects of the increased diffusivity will be counteracted, thereby inducing the formation of a skin. A modified Peclet number, Pe, using Dcoop, is proposed, so that the presence of salt is explicitly considered. This modified Pe is able to predict the nonuniformity in drying that leads to skin formation